The impact of wind power growth and hydrological uncertainty on financial losses from oversupply events in hydropower-dominated systems. (15th May 2017) - Su, Yufei; Kern, Jordan D.; Characklis, Gregory W.
Highlights: Oversupply can lead to financial losses when renewable energy is curtailed. Oversupply losses will increase as a function of installed wind capacity. Adding transmission capacity is not a cost effective solution to oversupply. Abstract: The rapid expansion of variable renewable energy (e.g., wind and solar) can make it more difficult to balance electricity supply and demand at a grid-scale. While much attention has focused on the risk of unexpected generation shortfalls, periods of oversupply (when supply is greater than demand) also present challenges that can lead to financial losses for utilities and/or consumers when renewable energy is "curtailed". A unique form of oversupply occurs in hydro-dominated systems. Although hydropower is thought to offer a highly flexible resource that can complement variable renewable energy, seasonal variability in streamflows and the presence of environmental regulations can create complex oversupply conditions if renewable energy is plentiful. In this study, an integrated hydro-economic model is developed to assess the frequency and severity of financial losses arising from oversupply in the U.S. Pacific Northwest, a hydro-dominated system with rapidly growing wind power generation. Present value losses over 25 years (2016–2040) are evaluated under several future scenarios including increased wind capacity, electricity price uncertainty, and expanded transmission capacity for moving excess electricity to export markets. Results indicate that oversupply losses will increase as a function of installed wind capacity, with the extent of this increase sensitive to future electricity prices. In the case of adding transmission capacity to alleviate oversupply losses, the cost of this infrastructure is substantially more than the associated reduction in losses and is therefore difficult to justify.